Therapy of spinal cord injury by folic acid polyethylene glycol amine-modified zeolitic imidazole framework-8 nanoparticles targeted activated M/Ms - Li, Qi; Guo, Yue; Xu, Chang; Sun, Jiachen; Zeng, Fanzhuo; Lin, Sen; Yuan, Yajiang (Frontiers in Bioengineering and Biotechnology, 2022)
Excessive neurotoxic microglia/macrophages (M1 M/Ms) reestablish the pro-inflammatory microenvironment that exacerbates motor and/or sensory dysfunction after spinal cord injury (SCI). Thus, M1 M/Ms-suppressed treatments may be effective strategies for SCI. However, the utilization of anti-inflammatory drugs for clinical approaches and biomedical researches has side-effects, such as nephrotoxicity and hepatotoxicity. In this study, we fabricated folic acid polyethylene glycol amine (FA-PEG)-modified zeolitic imidazole framework-8 (ZIF-8) nanoparticles (FA-PEG/ZIF-8) and found that it effectively recovered function in vivo. FA-PEG/ZIF-8 treatment significantly eliminated M1 M/Ms without targeting other nerve cells and downregulated inflammation in the injured lesion. Furthermore, FA-PEG/ZIF-8 posed little toxicity on SCI mice compared to normal mice. These results showed that FA-PEG/ZIF-8 injection impaired M1 M/Ms during the early SCI recovery.